(untitled) (San Francisco, CA, 2006)
School Health Services and Programs offers an introduction to the components of successful school health programs. It contains a comprehensive review article by Julia Graham Lear, reprints of important and influential articles and reports in the field and of a book chapter summarizing the Robert Wood Johnson Foundation’s work to improve school health, and summaries of relevant Robert Wood Johnson Foundation grant results reports. The book emphasizes the relationship between school health and community health, and the importance of evidence-based policy in developing strategies to improve children’s health
Keywords: School health services,Dịch vụ sức khỏe học đường; United States